Risks and Benefits of Kidney Transplantation during the COVID-19 Pandemic: Transplant or Not Transplant?. Issue 7 (29th July 2021) - Ajaimy, Maria; Liriano-Ward, Luz; Graham, Jay A.; Akalin, Enver
Abstract: COVID-19 has significantly affected the transplant community, by leading to decreased transplant activity and increased waiting list time. As expected, COVID-19 causes substantial mortality in both ESKD and kidney transplant populations. This is due to underlying CKD and a high prevalence of comorbid conditions, such as diabetes mellitus, hypertension, and cardiovascular disease in this group. Transplant programs have faced the difficult decision of weighing the risks and benefits of transplantation during the pandemic. On one hand, there is a risk of COVID-19 exposure leading to infection while patients are on maximum immunosuppression. Alternatively, there are risks of delaying transplantation, which will increase waitlist times and may lead to waitlist-associated morbidity and mortality. Cautious and thoughtful selection of both the recipient's and donor's post-transplant management has been required during the pandemic, to mitigate the risk of morbidity and mortality associated with COVID-19. In this review article, we aimed to discuss previous publications related to clinical outcomes of COVID-19 disease in kidney transplant recipients, patients with ESKD on dialysis, or on the transplant waiting list, and the precautions transplant centers should take in decision making for recipient and donor selection and immunosuppressive management during the pandemic. Nevertheless, transplantation in this milieu does seem to be the correct decision, with careful patient and donor selection and safeguard protocols for infection prevention. Each center should conduct risk assessment on the basis of the patient's age and medical comorbidities, waitlist time, degree of sensitization, cold ischemia time, status of vaccination, and severity of pandemic in their region.